2012
DOI: 10.1063/1.4744914
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale magnetic tunnel junction sensors with perpendicular anisotropy sensing layer

Abstract: A nano-scale linear magnetoresistance sensor is demonstrated using magnetic tunnel junctions with an in-plane magnetized reference layer and a sensing layer with interfacial perpendicular anisotropy. We show that the sensor response depends critically on the thickness of the sensing layer since its perpendicular anisotropy is significantly associated with thickness. The optimized sensors exhibit a large field sensitivity of up to 0.02% MR/Oe and a high linear field range of up to 600 Oe. These findings imply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 19 publications
3
34
0
1
Order By: Relevance
“…The latter presents simultaneously both types of responses, sharp hysteretic ones with TMR values up to ∼200% (t > t critical ) and linear responses with TMR values down to 40%, translating the thin CoFeB evolution from the ferromagnetic to the SPMlike regime (t ≤ t critical ). This transition is also illustrated in the inset of Figure 20a with the abrupt drop in coercive field at t critical ∼ 1.45 nm which is in accordance with other reported values [79][80][81][92][93][94]. Tsai et al estimated ∼23 nm as the average lateral size of the ferromagnetic particles at the sensing layer [94] while Shen et al obtained 40-120 nm [95] which for the given t critical implies that the clusters have a pancake-like shape.…”
Section: -P11supporting
confidence: 78%
See 3 more Smart Citations
“…The latter presents simultaneously both types of responses, sharp hysteretic ones with TMR values up to ∼200% (t > t critical ) and linear responses with TMR values down to 40%, translating the thin CoFeB evolution from the ferromagnetic to the SPMlike regime (t ≤ t critical ). This transition is also illustrated in the inset of Figure 20a with the abrupt drop in coercive field at t critical ∼ 1.45 nm which is in accordance with other reported values [79][80][81][92][93][94]. Tsai et al estimated ∼23 nm as the average lateral size of the ferromagnetic particles at the sensing layer [94] while Shen et al obtained 40-120 nm [95] which for the given t critical implies that the clusters have a pancake-like shape.…”
Section: -P11supporting
confidence: 78%
“…The latter can result in a linear response to in-plane magnetic fields [80,81]. Figure 20a shows the progress of patterned MTJ transfer curves with decreasing sensing layer thickness.…”
Section: -P11mentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain these characteristics and to suppress hysteresis in magnetoresistance (MR) curves, MTJs with spin-valve-type structures of CoFeB sensing layers showing perpendicular magnetic anisotropy (PMA) have been investigated. [1][2][3] We have also reported that the MTJs of CoFeB sensing layers of various thicknesses, which show PMA at the MgO/CoFeB interface, 4 can suppress the hysteresis. 3 Ta capping layers have been applied to these reported MTJs, in which CoFeB sensing layers have only one interface with MgO films, and the characteristics of the MTJs of the sensing layers showing partial PMA strongly depend on the thickness of the sensing layer.…”
Section: Introductionmentioning
confidence: 91%